Gerenciamento de resultados e sua relação com a adoção da revisão da vida útil do ativo: um estudo empírico com as empresas listadas no IBOVESPA - Cruz, Bruno Alexandre (2011)
Earnings management and its relationship with the adoption of changing the estimated useful life of long lived assets: a empirical research with the companies listed on IBOVESPA Under assumption of agency theory, accouting choice theory and premises of earnings management the objects of this research is to understand the relationship between earnings management by changing the estimated useful life of long lived assets and the introduction of the review of useful life of assets in Brazil under the CPC 27 Ativo Imobilizado and the ICPC 10 ( Interpretação Técnica 10 ) by the public companies in their issued financial statements for the year ended December 31, 2010. The foundations for the hypotheses considered in this research were based on: (i) if the companies listed on IBOVESPA that adopted the depreciation rates suggested by the Secretaria da Receita Federal (SRF) had boosted the main accouting performances and (ii) if the companies that adopted the revised depreciation rates under the ICPC 10 had boosted the main accouting performances. The univariate regression model was used empirically to estimate this discretionary Accruals, which are the proxy of changed discretionary value of accounting earnings. The study showed that Brazilian companies that adopted different depreciation rates, instead of the ones recommended by the Secretaria da Receita Federal ( SRF ), obtained increased financial ratios than the companies that adopted the SRF depreciation rates. In addition, the qualitative samples analysis demonstrated the intrinsic relation between earnings management and lower levels of corporate governance